The Moderating Effect of Employee Political Skill on the Link between Perceptions of a Victimizing Work Environment and Job Performance - Bentley, Jeffrey R.; Treadway, Darren C.; Williams, Lisa V.; Gazdag, Brooke Ann; Yang, Jun (Frontiers in Psychology, 2017)
Research has generally revealed only a weak link, if any at all, between victimization-related experiences and job performance. Drawing on the commonly used conservation of resources perspective, we argue that such inconsistent evidence in the organizational literature stems from an over-focus on personal resources at the expense of considering the role of social resources. Victimization is an interpersonal phenomenon with social ramifications. Its effects may be better captured when measured from the standpoint of the social environment, and analyzed relative to an employee’s capacity to effectively regulate those social resources. With the latter capacity being encapsulated by the construct of political skill, we conducted two studies to explore the moderating influence of employee political skill on the relationship between employee perceptions of a victimizing work environment and employee task performance. In Study 1, employees with low political skill exhibited reduced task performance when perceiving a victimizing environment, and this link was found to be mediated by tension in Study 2. Those with high political skill exhibit no change in performance across victimization perceptions in Study 2, yet an increase in performance in Study 1. We discuss our findings relative to the victimization and political skill literatures.